THE LOST YEARS OF MERLIN: A SCHOLARLY EXPLORATION OF T. A. BARRON’S ARTHURIAN FANTASY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
T.A. Barron’s The Lost Years of Merlin series (1996–2000) stands as a significant contribution to the genre of young adult fantasy, drawing upon Arthurian legend to explore themes of self-discovery, destiny, and moral responsibility. This article seeks to examine the narrative, thematic, and cultural implications of Barron’s work, focusing on the protagonist Merlin’s journey from boyhood to the legendary wizard of Camelot. By engaging with both literary analysis and historical context, this article will shed light on how Barron’s retelling revitalizes the Arthurian mythos for a modern audience, while presenting a nuanced character study of Merlin, his companions, and his inner conflicts.